PENERAPAN KURIKULUM MERDEKA DI SMP NEGERI 3 TONDANO - Fitrianingrum, Aufa Maulida; Mundiahi, Oksan Prasetio; Assa, Yunice Feni (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2024)
This study aims to examine the implementation of the Merdeka Curriculum at SMP Negeri 3 Tondano in the learning process. The research employed a descriptive qualitative method. Data collection techniques included field observation, interviews, and document analysis. Primary data sources for this study were teachers, while secondary data included supporting materials such as the school profile, KOSP documents, teaching modules, and school reports. The findings indicated that SMP Negeri 3 Tondano has implemented the Merdeka Curriculum during the first semester of the 2024/2025 academic year, gradually replacing the 2013 Curriculum. The implementation focuses on project-based learning, differentiation, and the strengthening of the Pancasila Student Profile. Collaboration among teachers, students, and parents, facilitated through the school committee, plays a significant role in supporting the success of the curriculum. Despite challenges such as adaptation from the previous curriculum and limited infrastructure, the school actively addresses these issues through teacher training and the use of technology. With a focused approach and regular evaluation, the Merdeka Curriculum is expected to produce graduates who are skilled, independent, and ready to contribute to the future.